Anti-permeation PVC (polyvinyl chloride) calendering film and production process thereof
By combining nitrogen-doped bentonite powder with titanium dioxide, the problem of aging of PVC pressure-release film in harsh environments is solved, its weather resistance and oxidation resistance are improved, service life is extended and good processing performance is maintained.
Patent Information
- Application Number
- CN202510150612.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-11
AI Technical Summary
When used outdoors, PVC pressure-release membrane is less weather-resistant and can easily turn yellow and age in harsh environments such as strong sunlight and rain, resulting in a decrease in service life.
By combining nitrogen-doped bentonite powder with titanium dioxide, the rheology of the resin is improved, the compatibility between the resin and bentonite is improved, and parabenzoic acid is avoided as a compatibility agent, thereby maintaining good processing performance at high temperatures.
The weather resistance, oxidation resistance and anti-permeability of the PVC pressure-retaining film are significantly improved, the service life is extended, and the processing performance degradation caused by the decomposition of the compatible agent at high temperatures is avoided.
Smart Images

Figure BDA0005267969690000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PVC rolled films, and in particular relates to an anti-permeation PVC rolled film and a production process thereof. Background Art
[0002] Polyvinyl chloride (PVC) and polyethylene (PE), polypropylene (PP), polystyrene (PS) and ABS resin are collectively referred to as the five general resins. PVC calendered film is a film with a certain thickness, width and surface smoothness prepared by subjecting PVC resin and filler to subsequent processes such as voltage, lamination, gluing, inflation, flocking and printing. Its thickness is generally less than 0.25mm and it has good anti-penetration effect. Depending on its use, it is now widely used in inflatable toys, inflatable boats, swimming rings, inflatable beds, umbrellas, stationery covers, tablecloths and shower curtains, etc.
[0003] When some PVC rolled film products are used as tablecloths outdoors, they are susceptible to erosion from the natural environment due to their poor weather resistance. They are prone to yellowing and aging when exposed to harsh environments such as strong sunlight and rain for a long time, thereby reducing their service life.
[0004] In order to improve the performance of PVC calendered film, it is generally necessary to add fillers and other additives during the production process. The Chinese patent with the announcement number CN107383421A announced a method for preparing titanium dioxide for PVC calendered film, which uses a three-phase mixture of far-infrared ceramic powder, zinc oxide and titanium dioxide, and is coated with a silicon dioxide layer, and further organically modified to obtain modified titanium dioxide. Through surface treatment with p-hydroxybenzoic acid and sodium silicate, p-hydroxybenzoic acid has a good dispersing effect on titanium dioxide, which promotes the compatibility of modified titanium dioxide with film resin. However, the processing temperature of some PVC calendered film products is relatively high, and p-hydroxybenzoic acid may be significantly decomposed at this temperature, resulting in a decrease in the compatibility of the above-mentioned titanium dioxide for calendered film with the PVC matrix and uneven distribution, thereby resulting in a decrease in the processing performance of the PVC calendered film. Summary of the invention
[0005] The object of the present invention is to provide an anti-permeation PVC rolled film and a production process thereof. By compounding nitrogen-doped bentonite powder with titanium dioxide, the bentonite can improve the rheological property of the resin, thereby improving the processing performance of the resin. By introducing nitrogen atoms into the lattice or surface of the bentonite, the charge state of the bentonite can be significantly affected, and the compatibility of the bentonite with the resin matrix can be improved. At the same time, there is no need to add p-hydroxybenzoic acid as a compatibilizer, and the film also has good processing performance, thereby avoiding the decomposition of the compatibilizer at a high temperature, which leads to a decrease in the processing performance of the product.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A production process for an anti-permeation PVC calendered film comprises the following steps:
[0008] Step 1: adding sulfonated composite bentonite powder, p-hydroxyaniline and deionized water into a reaction kettle, stirring for 1-2 hours at 50-60° C. and 400-500 r / min, adding epichlorohydrin into the reaction kettle, stirring for 30-50 minutes at 50-60° C. and 400-500 r / min, adding 50-60wt% potassium hydroxide solution and tetrabutylammonium bromide into the reaction kettle, stirring for 24-26 hours at 50-60° C. and 400-500 r / min, filtering, washing the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum drying at 60-80° C. for 1-2 hours to obtain epoxy composite bentonite powder.
[0009] Step 2: Mix the fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate in a mass ratio of 90-100:10-15:1-3:2-3, and then mix and plasticize for 10-12 minutes at 180-190°C using a double-roll mill. Roll the obtained sheet into shape at 180-190°C using a four-roll calendering device. Add fluorine-free waterproof and oil-proof agent at a rate of 200-300mL / m 2 The amount of the coating agent is sprayed on the surface of the formed intraocular pressure membrane, dried at 50-60°C for 50-80 minutes, cooled and rolled up to obtain an anti-permeation PVC rolled membrane.
[0010] Furthermore, in step 1, the dosage ratio of the sulfonated composite bentonite powder, p-hydroxyaniline, deionized water, epichlorohydrin, potassium hydroxide and tetrabutylammonium bromide is 1-2kg: 2-3kg: 5-6L: 1-2L: 500-600mL: 300-400mL.
[0011] Furthermore, in step 2, the mass ratio of the fluorinated modified PVC resin, the epoxy composite bentonite powder, the methyl tin stabilizer and the zinc stearate is 90-100:10-15:1-3:2-3.
[0012] Further, the sulfonated composite bentonite powder is prepared by the following steps:
[0013] Step 1: Add tetrabutyl titanate, 50-60wt% ethanol solution and 3-4mol / L acetic acid solution into a reactor, stir at 60-70℃ and 500-600r / min for 40-60min, then add nitrogen-doped bentonite powder, continue stirring for 24-26h, filter, wash the filter cake with anhydrous ethanol 2-3 times, vacuum dry, transfer to a muffle furnace, heat to 350-370℃, introduce air, calcine for 1-2h, heat to 600-650℃ at 5-6℃ / min under argon protection, keep warm for 2-3h, cool naturally, and obtain nitrogen-doped composite bentonite powder.
[0014] Step 2: Add nitrogen-doped composite bentonite powder, 10-15% by mass sulfuric acid and 8-13% by mass nitric acid into a reactor, stir at 60-80° C. and 500-600 r / min for 30-40 min, filter, wash the filter cake with deionized water until the pH value of the last washing liquid is neutral, and vacuum dry to obtain acidified composite bentonite powder.
[0015] Step 3: Transfer the acidified composite bentonite powder to a mixed solution of 3-mercaptopropyltrimethoxysilane and ethanol, stir for 30-40 min at 60-80° C. and 500-600 r / min, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry at 60-80° C. for 1-2 h to obtain a mercapto-modified composite bentonite powder.
[0016] Step 4: Place the thiol-modified composite bentonite powder in a 20-30wt% hydrogen peroxide solution, add a 0.5-0.6M sodium hydroxide solution to a pH value of 9-10, filter, wash the filter cake with deionized water and ethanol 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain a sulfonated composite bentonite powder.
[0017] Furthermore, the dosage ratio of tetrabutyl titanate, ethanol, acetic acid and nitrogen-doped bentonite powder is 3-4 kg: 4-5 L: 500-600 mL: 2-3 kg.
[0018] Furthermore, the usage ratio of the nitrogen-doped composite bentonite powder, sulfuric acid and nitric acid is 2-3 kg: 2-3 L: 800-1000 mL.
[0019] Furthermore, the dosage ratio of the acidified composite bentonite powder, 3-mercaptopropyltrimethoxysilane and ethanol is 1-2 kg: 800-900 mL: 4-5 L.
[0020] Furthermore, the usage ratio of the mercapto-modified composite bentonite powder and hydrogen peroxide is 1-2kg:2-3L.
[0021] Further, the fluorinated modified PVC resin is prepared by the following steps:
[0022] Perfluorooctyl ethyl acrylate, 4-hydroxybutyl vinyl ether, deionized water and anhydrous ethanol are added to a reaction kettle, stirred at 57-65° C. and 500-600 r / min for 1-2 hours, 1,4-dioxane, di(2-ethylhexyl) peroxydicarbonate as an initiator and dilauroyl peroxide are added to the reaction kettle, and vinyl chloride is added to the reaction kettle under nitrogen protection, stirred at 57-65° C. and 500-600 r / min for 4-5 hours, and a methanol solution with a mass concentration of 20-30% is gradually added dropwise to the reaction kettle. After the addition is completed, the mixture is allowed to stand for 24-26 hours, filtered, and the filter cake is washed with anhydrous methanol for 2-3 times, and vacuum dried at 60-80° C. for 1-2 hours to obtain a fluorinated modified PVC resin.
[0023] Furthermore, the usage ratio of perfluorooctyl ethyl acrylate, 4-hydroxybutyl vinyl ether, deionized water, anhydrous ethanol, 1,4-dioxane, di(2-ethylhexyl) peroxydicarbonate, dilauroyl peroxide, vinyl chloride and methanol is 500-600mL:800-900g:2-3L:2-3L:4-5L:800-900g:500-600g:7-8kg:8-9L.
[0024] Beneficial effects of the present invention:
[0025] 1. The anti-penetration PVC rolled film prepared by the present invention has good weather resistance, oxidation resistance and anti-penetration properties, and can be used outdoors for a long time under harsh environments such as strong sunlight and rain; by compounding nitrogen-doped bentonite powder with titanium dioxide, the bentonite can improve the rheological properties of the resin, thereby improving the processing performance of the resin; by introducing nitrogen atoms into the lattice or surface of the bentonite, the charge state of the bentonite can be significantly affected, and the compatibility of the bentonite with the resin matrix can be improved; at the same time, there is no need to add p-hydroxybenzoic acid as a compatibilizer, and the film also has good processing performance, thereby avoiding the decomposition of the compatibilizer at a high temperature and causing the processing performance of the product to decrease.
[0026] The fluorinated modified PVC resin of the present invention is grafted into the polymer chain of the PVC resin by combining the hydroxyl groups of 4-hydroxybutyl vinyl ether with the hydrolyzed perfluorooctyl ethyl acrylate under hydrothermal conditions. The fluorine atom has extremely strong electronegativity and chemical stability, so that the PVC calendered film has good barrier properties, thereby being able to prevent water penetration.
[0027] 2. The epoxy composite bentonite powder of the present invention introduces phenolic hydroxyl groups into the epoxy composite bentonite powder by reacting the amine groups on p-hydroxyaniline with the sulfonic acid groups on the surface of the sulfonated composite bentonite powder. The H protons in the phenolic hydroxyl groups are easily captured by free radicals, which prevents the chain reaction of the free radicals and forms oxygen free radicals. The oxygen free radicals can react with other free radicals, effectively improving the oxidation resistance of the rolled film and thus slowing down the aging of the rolled film. Compared with directly adding antioxidants or anti-aging agents, the anti-aging components in the PVC rolled film under this production process will not migrate, and the anti-aging effect is more durable.
[0028] 3. The surface of bentonite is doped with nitrogen, and the nitrogen element is introduced into the lattice of titanium dioxide to improve the spectral absorption range and light absorption capacity, thereby improving the reflection and scattering of ultraviolet rays, further reducing the aging rate of PVC calendered film. Different from the traditional direct addition of antioxidants, it effectively avoids the migration in the resin matrix caused by direct addition, thereby reducing the service life, stability and safety of the product; the epoxy bentonite molecule contains epoxy groups, which can capture the free radicals C l separated during the degradation process of PVC - , thereby terminating the free radical reaction of PVC degradation, slowing down the degradation rate, and improving the stability of the PVC calendered film. This stabilizing effect enables the PVC calendered film to maintain better performance during use and extend its service life. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1: A production process for an anti-permeation PVC calendered film, comprising the following steps:
[0031] S1: 500mL perfluorooctyl ethyl acrylate, 800g 4-hydroxybutyl vinyl ether, 2L deionized water and 2L anhydrous ethanol were added to a reactor, stirred at 57°C and 500r / min for 1h, 4L 1,4-dioxane, 800g di(2-ethylhexyl) peroxydicarbonate as an initiator and 500g dilauroyl peroxide were added to the reactor, and under nitrogen protection, 7kg vinyl chloride was added to the reactor, stirred at 57°C and 500r / min for 4h. After the reaction was terminated, 8L of a 20% methanol solution was gradually added dropwise to the reactor. After the addition was completed, it was allowed to stand for 24h, filtered, and the filter cake was washed twice with anhydrous methanol and dried under vacuum at 60°C for 1h to obtain a fluorinated modified PVC resin.
[0032] After hydrolysis, perfluorooctyl ethyl acrylate is combined with the hydroxyl group of 4-hydroxybutyl vinyl ether under hydrothermal conditions and grafted into the polymer chain of PVC resin to obtain fluorinated modified PVC resin.
[0033] S2: Add 4 kg of bentonite powder with a particle size of 2-3 μm, 1 kg of urea and 8 L of anhydrous ethanol into a reactor, stir at 50°C and 400 r / min for 4 h, filter, wash the filter cake twice with deionized water, transfer to a muffle furnace, heat to 500°C, keep warm for 4 h, and cool naturally to obtain nitrogen-doped bentonite powder.
[0034] Nitrogen doping can significantly affect the charge state, surface polarity and functional group types of bentonite by introducing nitrogen atoms into the lattice or surface of bentonite, affecting its particle morphology and particle size distribution. These changes act together on the interaction interface between bentonite and the resin matrix, which can improve the compatibility of bentonite and the resin matrix.
[0035] S3: Add 3kg of tetrabutyl titanate, 4L of 50% ethanol solution by mass fraction and 500mL of 3 mol / L acetic acid solution into the reactor, stir at 60°C and 500r / min for 40min, then add 2kg of nitrogen-doped bentonite powder, continue stirring for 24h, filter, wash the filter cake twice with anhydrous ethanol, vacuum dry at 60°C for 1h, transfer to a muffle furnace, heat to 350°C, introduce air, calcine for 1h, heat to 600°C at 5°C / min under argon protection, keep warm for 2h, cool naturally to obtain nitrogen-doped composite bentonite powder.
[0036] Depositing titanium dioxide on the surface of nitrogen-doped bentonite powder and calcining it can promote the crystal transformation of TiO2 from an unstable crystal form to a stable one.
[0037] S4: 2 kg nitrogen-doped composite bentonite powder, 2 L sulfuric acid with a mass fraction of 10% and 800 mL nitric acid with a mass fraction of 8% were added to a reactor, stirred at 60 ° C and 500 r / min for 30 min, filtered, and the filter cake was washed with deionized water until the pH value of the last washing liquid was neutral, and vacuum dried to obtain an acidified composite bentonite powder; 1 kg of the acidified composite bentonite powder was transferred to 800 mL The mixed solution of 3-mercaptopropyltrimethoxysilane and 4L ethanol was stirred at 60°C and 500r / min for 30min, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 60°C for 1h to obtain a thiol-modified composite bentonite powder; 1kg of the thiol-modified composite bentonite powder was placed in 2L 20wt% hydrogen peroxide solution, a 0.5M sodium hydroxide solution was added to a pH value of 9, filtered, the filter cake was washed twice with deionized water and ethanol, and vacuum dried at 60°C for 1h to obtain a sulfonated composite bentonite powder.
[0038] The nitrogen-doped composite bentonite powder is treated by acidification and then placed in a 3-mercaptopropyltrimethoxysilane solution to graft the mercapto groups onto the surface of the nitrogen-doped bentonite. The mercapto groups are then oxidized to obtain sulfonic acid groups.
[0039] S5: 1 kg of sulfonated composite bentonite powder, 2 kg of p-hydroxyaniline and 5 L of deionized water were added to a reactor, stirred at 50°C and 400 r / min for 1 h, 1 L of epichlorohydrin was added to the reactor, stirred at 50°C and 400 r / min for 30 min, 500 mL of 50 wt% potassium hydroxide solution and 300 mL of tetrabutylammonium bromide were added to the reactor, stirred at 50°C and 400 r / min for 24 h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried under vacuum at 60°C for 1 h to obtain epoxy composite bentonite powder.
[0040] The phenolic hydroxyl group is introduced into the epoxy composite bentonite powder by reacting the amine group on the p-hydroxyaniline with the sulfonic acid group on the surface of the sulfonated composite bentonite powder. The H proton in the phenolic hydroxyl group is easily captured by the free radical, which prevents the chain reaction of the free radical and forms oxygen free radicals. The oxygen free radicals can react with other free radicals, thereby slowing down the aging of the rolled film and effectively improving the oxidation resistance of the rolled film. The epoxy-modified porous bentonite powder is obtained by reacting epichlorohydrin with the hydroxyl group on the surface of the sulfonated composite bentonite powder.
[0041] S6: Fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate were mixed in a mass ratio of 90:10:1:2, and then mixed and plasticized for 10 min at 180°C using a two-roll mill. The obtained sheet was calendered at 180°C using a four-roll calendering device. The fluorine-free water and oil repellent was added at 200 mL / m 2 The amount of the coating agent is sprayed on the formed sheet, dried at 50°C for 50 minutes, cooled and rolled up to obtain an anti-permeation PVC calendered film.
[0042] Example 2: A production process for an anti-permeation PVC calendered film, comprising the following steps:
[0043] S1: 550mL perfluorooctyl ethyl acrylate, 850g 4-hydroxybutyl vinyl ether, 2.3L deionized water and 2.3L anhydrous ethanol were added to a reactor, stirred at 60°C and 550r / min for 1.2h, 4.5L 1,4-dioxane, 850g di(2-ethylhexyl) peroxydicarbonate as an initiator and 550g dilauroyl peroxide were added to the reactor, and under nitrogen protection, 7.8kg vinyl chloride was added to the reactor, stirred at 60°C and 550r / min for 4.5h. After the reaction was terminated, 8.9L of a methanol solution with a mass concentration of 25% was gradually added to the reactor. After the addition was completed, it was allowed to stand for 25h, filtered, and the filter cake was washed twice with anhydrous methanol and dried under vacuum at 70°C for 1.2h to obtain a fluorinated modified PVC resin.
[0044] S2: Add 4.5 kg of bentonite powder with a particle size of 2-3 μm, 1.2 kg of urea and 8.9 L of anhydrous ethanol into a reactor, stir at 55°C and 450 r / min for 4.5 h, filter, wash the filter cake twice with deionized water, transfer to a muffle furnace, heat to 530°C, keep warm for 5 h, and cool naturally to obtain nitrogen-doped bentonite powder.
[0045] S3: Add 3.4 kg of tetrabutyl titanate, 4.5 L of 55% ethanol solution by mass fraction and 550 mL of 3 mol / L acetic acid solution into the reactor, stir at 65 ° C and 550 r / min for 50 min, then add 2.3 kg of nitrogen-doped bentonite powder, continue stirring for 25 h, filter, wash the filter cake twice with anhydrous ethanol, vacuum dry at 70 ° C for 1.2 h, transfer to a muffle furnace, heat to 360 ° C, pass air, calcine for 1.2 h, and under argon protection, heat to 630 ° C at 5 ° C / min, keep warm for 2.3 h, and cool naturally to obtain nitrogen-doped composite bentonite powder.
[0046] S4: 2.3 kg of nitrogen-doped composite bentonite powder, 2.3 L of 13% sulfuric acid and 900 mL of 10% nitric acid were added to a reactor, stirred at 70°C and 550 r / min for 35 min, filtered, the filter cake was washed with deionized water until the pH value of the last washing liquid was neutral, and vacuum dried to obtain an acidified composite bentonite powder; 1.2 kg of the acidified composite bentonite powder was transferred to a mixed solution of 850 mL of 3-mercaptopropyltrimethoxysilane and 4.5 L of ethanol, stirred at 70°C and 550 r / min for 35 min, filtered, the filter cake was washed with deionized water twice, and vacuum dried at 70°C for 1.2 h to obtain a thiol-modified composite bentonite powder; 1.2 kg of the thiol-modified composite bentonite powder was placed in 2.3 L A 0.55 M sodium hydroxide solution was added to a 25 wt % hydrogen peroxide solution to a pH value of 9, and the solution was filtered. The filter cake was washed twice with deionized water and ethanol, and dried under vacuum at 70° C. for 1.2 h to obtain a sulfonated composite bentonite powder.
[0047] S5: 1.2 kg of sulfonated composite bentonite powder, 2.3 kg of p-hydroxyaniline and 5.6 L of deionized water were added into a reactor, stirred at 55°C and 450 r / min for 1.2 h, 1.2 L of epichlorohydrin was added into the reactor, stirred at 55°C and 450 r / min for 40 min, 550 mL of 55 wt% potassium hydroxide solution and 350 mL of tetrabutylammonium bromide were added into the reactor, stirred at 55°C and 450 r / min for 25 h, filtered, washed the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dried under vacuum at 70°C for 2 h to obtain epoxy composite bentonite powder.
[0048] S6: Fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate were mixed in a mass ratio of 95:13:2:2, and then mixed and plasticized for 11 minutes at 185°C using a two-roll mill. The obtained sheet was calendered at 185°C using a four-roll calendering device. The fluorine-free waterproof and oil-proof agent was added at a rate of 250 mL / m 2 The amount of the coating agent is sprayed on the formed sheet, dried at 55°C for 70 minutes, cooled and rolled up to obtain an anti-permeation PVC calendered film.
[0049] Embodiment 3: A production process of an anti-permeation PVC calendered film, comprising the following steps:
[0050] S1: 600mL perfluorooctyl ethyl acrylate, 900g 4-hydroxybutyl vinyl ether, 3L deionized water and 3L anhydrous ethanol were added to a reactor, stirred at 65°C and 600r / min for 2h, 5L 1,4-dioxane, 900g di(2-ethylhexyl) peroxydicarbonate as an initiator and 600g dilauroyl peroxide were added to the reactor, and under nitrogen protection, 8kg vinyl chloride was added to the reactor, stirred at 65°C and 600r / min for 5h. After the reaction was terminated, 9L of a 30% methanol solution was gradually added dropwise to the reactor. After the addition was completed, it was allowed to stand for 26h, filtered, and the filter cake was washed 3 times with anhydrous methanol and dried under vacuum at 80°C for 2h to obtain a fluorinated modified PVC resin.
[0051] S2: Add 5 kg of bentonite powder with a particle size of 2-3 μm, 2 kg of urea and 9 L of anhydrous ethanol into a reactor, stir at 60°C and 500 r / min for 5 h, filter, wash the filter cake with deionized water 3 times, transfer to a muffle furnace, heat to 550°C, keep warm for 6 h, and cool naturally to obtain nitrogen-doped bentonite powder.
[0052] S3: Add 4 kg of tetrabutyl titanate, 5 L of 60% ethanol solution by mass fraction and 600 mL of 4 mol / L acetic acid solution into the reactor, stir at 70 ° C and 600 r / min for 60 min, then add 3 kg of nitrogen-doped bentonite powder, continue stirring for 26 h, filter, wash the filter cake with anhydrous ethanol 3 times, vacuum dry at 80 ° C for 2 h, transfer to a muffle furnace, heat to 370 ° C, pass air, calcine for 2 h, and under argon protection, heat to 650 ° C at 6 ° C / min, keep warm for 3 h, and cool naturally to obtain nitrogen-doped composite bentonite powder.
[0053] S4: 3 kg of nitrogen-doped composite bentonite powder, 3 L of 15% sulfuric acid and 1000 mL of 13% nitric acid were added to a reactor, stirred at 80 °C and 600 r / min for 40 min, filtered, and the filter cake was washed with deionized water until the pH value of the last washing liquid was neutral, and vacuum dried to obtain an acidified composite bentonite powder; 2 kg of the acidified composite bentonite powder was transferred to 900 mL The mixed solution of 3-mercaptopropyltrimethoxysilane and 5L ethanol was stirred at 80°C and 600r / min for 40min, filtered, the filter cake was washed with deionized water for 3 times, and vacuum dried at 80°C for 2h to obtain a thiol-modified composite bentonite powder; 2kg of the thiol-modified composite bentonite powder was placed in 3L 30wt% hydrogen peroxide solution, a 0.6M sodium hydroxide solution was added to a pH value of 10, filtered, the filter cake was washed with deionized water and ethanol for 3 times, and vacuum dried at 80°C for 2h to obtain a sulfonated composite bentonite powder.
[0054] S5: 2kg of sulfonated composite bentonite powder, 3kg of p-hydroxyaniline and 6L of deionized water were added into a reactor, stirred at 60°C and 500r / min for 2h, 2L of epichlorohydrin was added into the reactor, stirred at 560°C and 500r / min for 50min, 600mL of 60wt% potassium hydroxide solution and 400mL of tetrabutylammonium bromide were added into the reactor, stirred at 60°C and 500r / min for 26h, filtered, washed the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dried under vacuum at 80°C for 2h to obtain epoxy composite bentonite powder.
[0055] S6: Fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate were mixed in a mass ratio of 100:15:3:3, and then mixed and plasticized for 12 minutes at 190°C using a two-roll mill. The obtained sheet was calendered at 190°C using a four-roll calendering device. The fluorine-free water and oil repellent was added at 300 mL / m 2 The amount of the coating agent is sprayed on the formed sheet, dried at 60°C for 80 minutes, cooled and rolled up to obtain an anti-permeation PVC calendered film.
[0056] Comparative Example 1: Based on Example 3, titanium dioxide specifically for PVC calendering film was prepared according to the preparation method with announcement number CN107383421A, replacing the epoxy composite bentonite powder in step S6, and the other steps remained unchanged to obtain an anti-permeability PVC calendering film.
[0057] Comparative Example 2: On the basis of Example 3, the nitrogen-doped bentonite powder in step S3 is replaced by the bentonite powder in step S3, and the other steps remain unchanged to obtain an impermeability-proof PVC rolled film.
[0058] Comparative Example 3: On the basis of Example 3, the epoxy composite bentonite powder in step S6 is replaced by the sulfonated composite bentonite powder in step S4, and the other steps remain unchanged to obtain an anti-permeability PVC rolled film.
[0059] Comparative Example 4: On the basis of Example 3, the nitrogen-doped composite bentonite powder in step S4 is replaced by the nitrogen-doped bentonite powder in step S2, and the other steps remain unchanged to obtain an impermeability-proof PVC rolled film.
[0060] Comparative Example 5: Based on Example 3, the fluorinated modified PVC resin in step S1 is replaced with a commercially available PVC resin, and the remaining steps remain unchanged to obtain an impermeability-proof PVC rolled film.
[0061] In the embodiments and comparative examples:
[0062] Perfluoroethyloctyl acrylate was purchased from Shandong Lubang Chemical Co., Ltd.
[0063] 4-Hydroxybutyl vinyl ether, 1,4-dioxane, di(2-ethylhexyl) peroxydicarbonate, dilauroyl peroxide, titanium tetrachloride and p-hydroxyaniline were purchased from Sigma-Aldrich.
[0064] The fluorine-free water and oil repellent was purchased from Shanghai Xiangjin Chemical Co., Ltd.
[0065] The performance test of the anti-permeability PVC rolled films prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was performed, and the results are shown in Table 1:
[0066] 1. Yellowing resistance test: The PVC rolled film was placed in a UV aging test chamber for 20 days. The three stimulus values X, Y, and Z of different samples before and after aging were tested using a YI-48A whiteness colorimeter in accordance with GB2409 standard. The yellowness index of the film sample before and after aging was calculated by the following formula: YI = [100 × (1.28X-1.06Z)] / Y, (ΔYI n = YI n-YI0, where ΔYI n is the change in the yellowness index of the sample after aging for n days; YI0 and YI n are the yellowness index values of the film sample before and after aging for n days, respectively).
[0067] 2. Mechanical properties test: Tested in accordance with GB / T1040-2006 standard.
[0068] 3. Ultraviolet transmittance: Use a UV-visible spectrophotometer for testing. The UV transmittance is expressed as the average transmittance of 315-380nm (UV-A) wavelength.
[0069] Table 1 Performance test table of anti-permeability PVC rolled film
[0070]
[0071] It can be seen from Table 1 that the tensile strength, elongation at break and transmittance of the anti-permeability PVC rolled film prepared in Examples 1 to 3 are significantly better than those in the comparative example, indicating that the PVC rolled film of the present invention has good tensile strength, impact resistance and anti-aging properties.
[0072] In Comparative Example 1, titanium dioxide specifically for PVC calendering film was prepared according to the preparation method with announcement number CN107383421A. Through surface treatment with p-hydroxybenzoic acid and sodium silicate, p-hydroxybenzoic acid has a good dispersing effect on titanium dioxide, which promotes the compatibility of modified titanium dioxide and film resin. However, after calendering at 190°C, p-hydroxybenzoic acid decomposes at this temperature, resulting in poor performance in performance tests and reduced processing performance of the product.
[0073] In Comparative Example 2, nitrogen-doped bentonite powder is replaced with bentonite powder. Nitrogen doping changes the surface properties of bentonite, improves its compatibility with the resin matrix, helps to evenly disperse bentonite in the resin, and reduces the occurrence of agglomeration. The addition of bentonite has a positive effect on the fluidity of the resin, improves the rheology of the resin, and thus improves the processing performance of the resin, so that the performance tests of tensile strength and elongation at break decrease. In addition, the nitrogen element can affect the crystal structure of titanium dioxide, increase the spectral absorption range and light absorption capacity, thereby increasing the reflection and scattering of ultraviolet rays, and further reducing the aging rate of the PVC rolled film. Therefore, after the loss of nitrogen doping, there is little effect on the ultraviolet light transmittance.
[0074] In Comparative Example 3, the epoxy composite bentonite powder is replaced with the sulfonated composite bentonite powder. The phenolic hydroxyl group is introduced into the epoxy composite bentonite powder. The H proton in the phenolic hydroxyl group is easily captured by the free radical, which prevents the chain reaction of the free radical and forms oxygen free radicals. The oxygen free radicals can react with other free radicals, thereby slowing down the aging of the rolled film and effectively improving the oxidation resistance of the rolled film. The epoxy bentonite molecule contains epoxy groups, which can capture the free radicals C l separated during the degradation process of PVC. - , thereby terminating the free radical reaction of PVC degradation, further slowing down the degradation rate and improving the stability of PVC calendered film.
[0075] In Comparative Example 4, the nitrogen-doped composite bentonite powder is replaced with nitrogen-doped bentonite powder. When ultraviolet rays irradiate the surface of titanium dioxide, the electrons in the titanium dioxide are excited. These excited electrons jump to a higher energy level, thereby absorbing ultraviolet rays. Titanium dioxide can also effectively scatter ultraviolet rays, thereby reducing the direct irradiation intensity of the PVC rolled film, further effectively improving the oxidation resistance of the rolled film, thereby avoiding aging of the PVC rolled film due to long-term ultraviolet irradiation. Therefore, after losing titanium dioxide, the ultraviolet light transmittance performance test performed the worst.
[0076] In Comparative Example 5, the mechanical properties of the anti-permeability PVC calendered film are slightly improved, while the yellowing resistance is improved. The fluorine atom has extremely strong electronegativity and chemical stability. The molecular chain structure of the fluorinated PVC resin is tight, which can improve the yellowing resistance of the PVC calendered film, but will cause its mechanical properties to decrease.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for an anti-permeation PVC calendered film, characterized in that: The steps include: Step 1: adding sulfonated composite bentonite powder, p-hydroxyaniline and deionized water into a reaction kettle, stirring at 50-60° C. and 400-500 r / min for 1-2 hours, then adding epichlorohydrin and stirring for 30-50 minutes, then adding 50-60wt% potassium hydroxide solution and tetrabutylammonium bromide into the reaction kettle, continuing to stir for 24-26 hours, filtering, washing the filter cake with deionized water and ethanol for 2-3 times, and vacuum drying to obtain epoxy composite bentonite powder; Step 2: Evenly mix the fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate, and then mix and plasticize for 10-12 minutes at 180-190°C using a double-roll open mill, and calender the obtained sheet using a four-roll calendering device at 180-190°C, and add the fluorine-free waterproof and oil-proof agent at a rate of 200-300mL / m 2 The amount of the coating agent is sprayed on the formed sheet, dried at 50-60°C for 50-80 minutes, cooled and rolled up to obtain an anti-permeation PVC calendered film.
2. The production process of a permeation-proof PVC rolled film according to claim 1, characterized in that: The dosage ratio of the sulfonated composite bentonite powder, p-hydroxyaniline, deionized water, epichlorohydrin, potassium hydroxide and tetrabutylammonium bromide in step 1 is 1-2kg: 2-3kg: 5-6L: 1-2L: 500-600mL: 300-400mL.
3. The production process of a permeation-proof PVC rolled film according to claim 1, characterized in that: In step 2, the mass ratio of fluorinated modified PVC resin, epoxy composite bentonite powder, methyl tin stabilizer and zinc stearate is 90-100:10-15:1-3:2-3.
4. The production process of a permeation-proof PVC rolled film according to claim 1, characterized in that: In step 1, the sulfonated composite bentonite powder is prepared by the following steps: The acidified composite bentonite powder is transferred to a mixed solution of 3-mercaptopropyltrimethoxysilane and ethanol, stirred at 60-80° C. and 500-600 r / min for 30-40 min, filtered, the filter cake is washed with deionized water 2-3 times, and vacuum dried to obtain a thiol-modified composite bentonite powder; the thiol-modified composite bentonite powder is placed in a 20-30wt% hydrogen peroxide solution, a 0.5-0.6M sodium hydroxide solution is added to a pH value of 9-10, filtered, the filter cake is washed with deionized water and ethanol 2-3 times, and vacuum dried to obtain a sulfonated composite bentonite powder; The dosage ratio of the acidified composite bentonite powder, 3-mercaptopropyltrimethoxysilane and ethanol is 1-2kg:800-900mL:4-5L; the dosage ratio of the mercapto-modified composite bentonite powder and hydrogen peroxide is 1-2kg:2-3L.
5. The production process of a permeation-proof PVC rolled film according to claim 4, characterized in that: The acidified composite bentonite powder is prepared by the following steps: Add nitrogen-doped composite bentonite powder, 10-15wt% sulfuric acid and 8-13wt% nitric acid into a reaction kettle, stir at 60-70°C and 500-600r / min for 30-40min, filter, wash the filter cake with deionized water until the pH value of the last washing liquid is neutral, and vacuum dry to obtain acidified composite bentonite powder; The usage ratio of the nitrogen-doped composite bentonite powder, sulfuric acid and nitric acid is 2-3kg: 2-3L: 800-1000mL.
6. The production process of a permeation-proof PVC rolled film according to claim 5, characterized in that: The nitrogen-doped composite bentonite powder is prepared by the following steps: Tetrabutyl titanate, 50-60wt% ethanol solution and 3-4mol / L acetic acid solution are added into a reaction kettle, stirred at 60-70°C and 500-600r / min for 40-60min, then nitrogen-doped bentonite powder is added, stirring is continued for 24-26h, filtered, the filter cake is washed with anhydrous ethanol 2-3 times, vacuum dried, transferred to a muffle furnace, heated to 350-370°C, air is introduced, calcined for 1-2h, heated to 600-650°C at 5-6°C / min under argon protection, kept warm for 2-3h, cooled naturally, and nitrogen-doped composite bentonite powder is obtained; The dosage ratio of tetrabutyl titanate, ethanol, acetic acid and nitrogen-doped bentonite powder is 3-4 kg: 4-5 L: 500-600 mL: 2-3 kg.
7. The production process of a permeation-proof PVC rolled film according to claim 6, characterized in that: The nitrogen-doped bentonite powder is prepared by the following steps: Add bentonite powder with a particle size of 2-3 μm, urea and anhydrous ethanol into a reactor, stir at 50-60° C. and 400-500 r / min for 4-5 hours, filter, wash the filter cake with deionized water 2-3 times, transfer to a muffle furnace, heat to 500-550° C., keep warm for 4-6 hours, and cool naturally to obtain nitrogen-doped bentonite powder; The usage ratio of the bentonite powder, urea and anhydrous ethanol is 4-5kg:1-2kg:8-9L.
8. The production process of a permeation-proof PVC rolled film according to claim 1, characterized in that: The fluorinated modified PVC resin described in step 2 is prepared by the following steps: Perfluorooctyl ethyl acrylate, 4-hydroxybutyl vinyl ether, deionized water and anhydrous ethanol are added to a reaction kettle, stirred at 57-65°C and 500-600r / min for 1-2h, 1,4-dioxane, di(2-ethylhexyl) peroxydicarbonate and dilauroyl peroxide are added to the reaction kettle, and under nitrogen protection, vinyl chloride is added to the reaction kettle, stirred at 57-65°C and 500-600r / min for 4-5h, 20-30wt% methanol solution is added dropwise to the reaction kettle, and the reaction kettle is allowed to stand for 24-26h, filtered, the filter cake is washed with anhydrous methanol for 2-3 times, and vacuum dried to obtain a fluorinated modified PVC resin.
9. The production process of a permeation-proof PVC rolled film according to claim 8, characterized in that: The dosage ratio of the perfluorooctyl ethyl acrylate, 4-hydroxybutyl vinyl ether, deionized water, anhydrous ethanol, 1,4-dioxane, di(2-ethylhexyl) peroxydicarbonate, dilauroyl peroxide, vinyl chloride and methanol is 500-600mL: 800-900g: 2-3L: 2-3L: 4-5L: 800-900g: 500-600g: 7-8kg: 8-9L.
10. An anti-permeation PVC calendering film, characterized in that: It is prepared by the production process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Vapor phase method for preparation of porous carrier supported nitrogen doped titanium dioxide
CN104248967A
Preparation method of modified bentonite PVC heat stabilizer
CN105949639A
Preparation method of titanium dioxide specially used for PVC calendaring film
CN107383421A
Preparation method of polyvinyl chloride plastic paste cross-linking agent
CN114133698A
Ultraviolet-proof PVC film and preparation method thereof
CN115093653A